Determinación de protocolos de medición de contaminantes producto de la combustión en vehículos a gasolina en la ciudad de Latacunga en el periodo académico 2019-2020. - Manobanda Panimboza, Johanna Nathaly (2020)
The purpose of this research is to provide key information on protocols to obtain technical data that reflects current situation regarding air pollution and quality deterioration generated by mobile sources of gasoline combustion at Latacunga city. Bibliographic information was compiled by reliable sources and obtained data by investigations carried out by Technical University of Cotopaxi Environmental career, of last three years were considered to make contamination probability percentage that would exist in this year by gas emissions of Carbon Monoxide CO and HC Hydrocarbons, taking into account that each year an average of 300 vehicles are evaluated through statistical tests applying established methodology NTE INEN 2 203, the equipment used to measure gases is AVL DiTest Gas 1000, it is detailed the use, handling and how it is structured, the security measures that must be taken at monitoring time, for this year there is a 50% probability of contamination reduction by CO and HC gases.